(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Sports refer to any competitive physical activity that individual do individually or in a team for thepurpose of amusement. The present paper examined the role of sports in national Development. Sportscan be seen to provide a useful way of creating an environment in which people can come together fornational development. Sports help in social development by resolving different social problems and byimproving social cohesiveness. On the basis of this paper it can be concluded that sports lead individualstowards well-being, which helps in national development.